Acute Myeloid Leukemia With Monosomal Karyotype: Morphologic, Immunophenotypic, and Molecular Findings. Issue 2 (1st August 2014) - Weinberg, Olga K.; Ohgami, Robert S.; Ma, Lisa; Seo, Katie; Ren, Li; Gotlib, Jason R.; Seetharam, Mahesh; Cherry, Athena; Arber, Daniel A.
Abstract: Objectives: Acute myeloid leukemia (AML) with monosomal karyotype (MK) recently has been reported to be associated with worse outcome than the traditional complex karyotype. Methods: In this retrospective study of 111 patients with AML, we identified 14 patients with MK (13% of all patients with AML) using the definition proposed by Breems et al. Results: Five (36%) of these 14 patients had a loss of a single chromosome in the presence of other structural abnormalities, and nine (64%) had a loss of two or more autosomal chromosomes. Patients with AML-MK presented at an older age, with lower bone marrow blasts, and their blasts less frequently expressed CD34. Most patients with AML-MK had morphologic multilineage dysplasia and were predominantly subclassified as having AML with myelodysplasia-related changes (AML-MRC). Molecular analysis showed a significant absence of NPM1 and FLT3 in patients with AML-MK. Conclusions: Outcome data showed that patients with AML-MK had significantly worse overall survival, disease-free survival, and complete response compared with the rest of the patients with AML as well as within the AML-MRC group.